THE EFFECT OF LISTENING EDM GENRE TO STUDENTS’ PRONUNCIATION - Yuliadi, Sigit; Pradana, Sultan Arief; Yugafiati, Rasi (PROJECT (Professional Journal of English Education), 2018)
Music dynamics is now infiltrated on the development of EDM (Electronic Dance Music) genre. Characteristics of those songs combine the beat, effects, and repetition of words. Those reasons make the EDM genre lovers dance. The genre is commonly found in bars, pubs, night clubs, performance and event venues (venues and appearances). This music genre is also found in radio and cable tv. Interestingly, the lyrics of the genre mostly use English. Although in this country, the lyrics sometimes are found in Bahasa. The lyrics in the EDM genre tend to be repetitive. Thus, the possibility of memorizing the lyrics in English may be higher. Memorize the lyrics in direct use when listening to the EDM genre, giving music lovers chance to produce acceptable pronunciation. The purpose of this study is to examine the mastery of English pronunciation through the lyrics of the EDM genre. The study involves three participants. This study uses descriptive qualitative method. The result of this research is that all participants feel helpful in improving English pronunciation ability by using EDM genre.